Teoria de médio alcance do diagnóstico de enfermagem padrão respiratório ineficaz em crianças com cardiopatias congênitas: teste empírico - Souza, Nayana Maria Gomes de (2022)
The main aim of this trial was to test in clinical practice the Middle Range Theory (MRT) on the Nursing diagnosis of Ineffective Breathing Pattern (IBP) in children with congenital heart disease. This is a cross-sectional study, carried out in a tertiary hospital institution, specialized in the diagnosis and treatment of heart diseases in the city of Fortaleza, Ceará. The study included 340 children, affected by congenital heart disease and admitted to the clinical inpatient unit and preoperative intensive care unit of the aforementioned hospital. To obtain the data, a data collection instrument and a protocol with operational and conceptual definitions of the stimuli and behaviors of MRT were used. The latent class model with adjusted random effects was used to determine IBP and measures of sensitivity and specificity of behaviors. Behavior was considered statistically significant if at least one of its confidence intervals (either for sensitivity or specificity) was greater and did not exceed 0.5. The relationship between observed behaviors and the level of clinical deterioration was analyzed using univariate logistic regressions. In addition, the application of the Mann-Whitney Test was used to verify which behaviors actually occurred among children older than two years of age. A univariate logistic regression analysis was performed for each IBP stimulus. Finally, log-linear models were tested to verify a possible joint relationship between focal and contextual stimuli on the IBP diagnosis. Based on a latent class model, it was found that 56.89% of the children with congenital heart diseases evaluated in this study manifested the IBP Nursing diagnosis. The behavior using accessory muscles to breathe expressed a high sensitivity and specificity value, and the behaviors that denoted the highest specificity values were dyspnea, nose flaring, respiratory muscle fatigue, bradypnea, tachypnea, altered thoracic excursion, changes in rhythm respiratory disorders, hypoxia and sleep-disordered breathing. The stimuli with the greatest impact for the occurrence of IBP were body position that inhibits lung expansion, physical effort, pain and age younger than two years. Furthermore, the statistical analysis of the stimulus-related proposition suggested a reclassification of the stimulus deformities in the chest wall. Thus, in the modified MRT, this stimulus is no longer contextual and becomes focal, as it directly influences the emergence of the IBP Nursing diagnosis. Consequently, the stimuli were reclassified as to the mechanism for the development of IBP in the studied population. On the other hand, the statistical verifications of the proposition related to the behaviors guided changes in the grouping of some concepts, when proceeded to the comparison with the theoretical structure. Based on the results of this study, the concepts and propositions of the Middle Range Theory on the Ineffective Breathing Pattern Nursing diagnosis in children with congenital heart disease were tested and, thus, the experiment contributed to the identification of evidence of validity of the IBP diagnosis, by allowing the identification of its structural elements and the explanation of the relationships between its components.